2023
DOI: 10.1002/jbmr.4824
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Cell Transcriptomic Atlas of Parathyroid Adenoma and Parathyroid Carcinoma

Abstract: Primary hyperparathyroidism is typically characterized by monoclonal parathyroid tumors that secrete an excessive amount of parathyroid hormone (PTH). However, the underlying pathogenesis of tumorigenesis remains unclear. We performed single‐cell transcriptomic analysis on five parathyroid adenoma (PA) and two parathyroid carcinoma (PC) samples. A total of 63,909 cells were divided into 11 different cell categories; endocrine cells accounted for the largest proportion of cells in both PA and PC, and patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…We have reported that iCAF marker genes including CFD, CXCL12, and IGF1 were enriched in PA samples and mCAF marker genes were highly expressed in PC samples. However, it was reported that the iCAF were mainly observed enriched in PC samples in one sc-RNAseq data incorporating 2 PA and 5 PA samples [19]. This opposite conclusion might result from the small cohort data, indicating the role of iCAF in parathyroid tumors needs further investigation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We have reported that iCAF marker genes including CFD, CXCL12, and IGF1 were enriched in PA samples and mCAF marker genes were highly expressed in PC samples. However, it was reported that the iCAF were mainly observed enriched in PC samples in one sc-RNAseq data incorporating 2 PA and 5 PA samples [19]. This opposite conclusion might result from the small cohort data, indicating the role of iCAF in parathyroid tumors needs further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…To comprehensively clarify the role of CAF, we manually collected signature genes of iCAF and mCAF [18]. The following genes were seen as markers of parathyroid parenchyma cells: PTH, CHGA, RARRES2, PVALB, CISD1, CASR, GCM2, KLCASR, VDR, LRP2, EPCAM, SLC17A5 [19][20][21]. The collected genes were rearranged and can be found in TableS2.…”
Section: Immune and Stromal Gene Collectionmentioning
confidence: 99%
“…76,77 However, whether it is involved in PA pathogenesis remains unclear, although the infiltration of immune cells into the PA microenvironment has been well documented. 28,78 Our analysis of stromal cells revealed that the PA microenvironment is markedly more proinflammatory than that of PG tissues. First, PA fibroblasts displayed primarily a phenotype similar to inflammatory cancer-associated fibroblasts 57,58 ; second, ECs in the PA microenvironment were strongly activated, expressing a range of genes necessary for immune cell extravasation; third, the frequency of myeloid cells was markedly higher in PA relative to PT tissues, and the inflammatory_response pathway was upregulated in PA macrophages; fourth, the angiogenesis pathway was enriched in T and NK cells from PAs compared with those from PGs, indicative of the inflammatory response, 79,80 although numerous hallmark gene signature pathways were downregulated, and last, PACs and PA fibroblasts, in contrast to PGCs and PG fibroblasts, received TNF signalling.…”
Section: Discussionmentioning
confidence: 97%
“…What are the mechanisms of the dysregulation of gene expression in PA stromal cells? Moreover, given the highly heterogeneous nature of PAs, 28,78…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation